Intimate Partner Violence-Related Emergency Department and Hospital Visits in California Following the ICD-10-CM Transition, 2016–2018 - Adhia, Avanti (Journal of interpersonal violence, 2023)
With the transition to the International Classification of Diseases and Related Health Problems, 10th Revision, Clinical Modification (ICD-10-CM), additional research is needed to understand which diagnostic codes for intimate partner violence (IPV) are being used. The current study examined characteristics of IPV visits and frequency of diagnostic codes to identify IPV in all emergency department (ED) and inpatient hospital visits for adults in California from 2016–2018, after ICD-10-CM implementation. Five ICD-10-CM codes outlined in the Uniform Data System Reporting Instructions were used to identify IPV. Fewer than 0.1% of visits (17,347 ED visits and 1,430 hospitalizations) included documentation of IPV. Visits with documented IPV were more common among patients who were younger, female, Black, primarily English-speaking, and publicly insured compared to visits with no documented IPV. There were fairly consistent patterns over time in the specific ICD-10-CM codes used for IPV between 2016 and 2018. Physical and sexual abuse were the most common codes for types of abuse. Among the 15 EDs and 15 hospitals in California with the highest volume of IPV visits, there was variability in the use of ICD-10-CM codes for IPV visits. Accurate documentation of IPV in administrative data may improve patient care and increase understanding of the burden and effects of IPV on individuals and communities.